PortaX Secure Automation System Using IoT: A Survey - Shivamadhu, Gagan Deep; Venkatesh, Aditya; Alva, Aishwarya; Nausheer, Daniya; Devi K. A, Sumithra (International Journal of Recent Technology and Applied Science (IJORTAS), 2020)
In recent times, everything around us is automated. People are looking to make things easier and easier day by day, by reducing the work they do, but not reduce the efficiency of work. The most important thing in this technically forward world, is, what we mentioned above i.e. Automation and Security. Travel needs a lot of automation in this day and age, especially Airports. The idea of a bag can check-in by itself, and tell us where it is and deprive us of the worry of continuously checking or thinking if the luggage is okay, is just a dream for most people.